Astragaloside IV confers neuroprotection against radiation-induced neuronal senescence via the ERK pathway - Ding, Yanping; Jiang, Chenxin; Chen, Lili; Liu, Xin; Shao, Baoping (Experimental neurology, 2025)
Various factors and mechanisms, including radiation, initiate cellular senescence and are concurrent with the progression of various neurodegenerative diseases. Radiation-induced chromosomal aberrations and DNA integrity damage impact the processes of cellular growth, maturation, and aging. Astragaloside IV (AS-IV) has been documented to display significant neuroprotective effects on inflammation, oxidative stress, and cellular apoptosis; however, the precise neuroprotective mechanism of AS-IV against neuronal aging remains unclear. In this study, radiation-induced senescence models in C57BL/6 mice, PC12 cells, and primary neuronal cells were established. SA-β-gal histochemistry, flow cytometric analysis, immunofluorescence technique, and Western blotting analysis were employed to investigate the underlying mechanism of AS-IV in mitigating the aging of the brain cells caused by exposure to radiation. Our findings revealed that radiation exposure may activate the ERK pathway, leading to an increase in SA-β-gal-positive cells, elevated p21 levels, and the arrest of neuronal cells in the G1/S phase. However, AS-IV has been observed to mitigate the radiation-driven proliferation of senescent cells, by downregulating p-ERK and CDK2 expression and upregulating p21 and RB expression in treatment, thereby alleviating the aging and cognitive impairment caused by radiation. Additionally, evidence of U0126 treatment further supports these findings. In summary, our study showed that AS-IV could protect mice from radiation-induced cognitive impairment and reduce cellular senescence by regulating the ERK pathway. •Radiation causes cellular senescence by activating ERK.•AS-IV effectively inhibits the radiation-induced increase in the number of senescent cells.•The ERK inhibitor U0126 protects against neurological damage by radiation.